The effect of steady-state ropinirole on plasma concentrations of digoxin in patients with Parkinson’s disease - Taylor, A (Blackwell Science Inc, 1999)
AIMS: The aim of this single-blind study was to assess the effect of ropinirole, a novel treatment for Parkinson’s disease, on the steady-state pharmacokinetics and safety of digoxin in 10 patients with Parkinson’s disease. METHODS: There were three parts to the study: digoxin once daily plus placebo three times daily for 1 week; digoxin once daily plus ropinirole three times daily for 6 weeks; and digoxin once daily plus placebo three times daily for 1 week. Serial blood samples were collected over 24 h at the end of each part of the study for pharmacokinetic assessment. Pre-dose blood samples were collected on specific days throughout the study to assess the attainment of steady-state plasma levels of digoxin. The primary endpoints were AUC(0, τ) and C(max) for digoxin. RESULTS: There was a mean decrease of 10% in digoxin AUC (0, τ) (90% CI: 0.79, 1.01) and a 25% decrease in digoxin C(max) (90% CI: 0.58, 0.97) when ropinirole was co-administered, compared with digoxin alone. C(min) plasma values for digoxin, however, were fairly constant throughout the study (point estimates 0.99, 95% CI: 0.85, 1.15). Changes in trough levels of digoxin are believed to be the most reliable way of assessing steady-state concentrations of digoxin, and therefore the clinical significance of an interaction. Changes in C(max) are too readily influenced by other factors. CONCLUSIONS: These results therefore indicate that on pharmacokinetic grounds no dose adjustment is necessary for digoxin co-administered with ropinirole.